Business Design for Making Organic Native Chicken Feed from Fermentation and Its Implementation in Biology Learning - Amalia Firdaus Yanti; Farah Halimah; Muhammad Naufal Mu'afa; Cindy Puspitasari; Ahmad Musthofa Anshori; Sajidan Sajidan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret, 2021)
Learning in the 21st century demands the increasing of students' creativity in solving problems in the environment. Creating products of economic value by applying the socio-scientific issue (SSI) learning approach can be applied in learning about biotechnology at the high school level. This study aimed to design a learning resource for teaching biotechnology which promoting the issue of SSI and nurturing the entrepreneurship of the student as well. Indonesia has the potential to develop native chicken farming to increase the economy status and people's income, but the productivity of native chickens is still low. To solve the problem, an organic feed based on rice bran and papaya leaves which have high nutritional content were introduced as one of the projects which can be run by high school students. To find the potential of papaya leaves and rice bran, a literature review had been done. The results shows that papaya leaves are rich in protease enzymes so that they can increase the digestibility of amino acids in chickens. Bran contains phytic acid as an antinutrient. The smell of ammonia cannot be separated from the problem of livestock. Production of feed from the fermentation of bacteria Bacillus subtilis and Lactobacillus bulgaricus can add phytase enzymes to increase nutrient absorption to accelerate the increase in chicken weight. Fermented feed is also able to inhibit bacteria that break down protein into ammonia so that the smell of feces disappears. Based on these findings, the learning activities for understanding the concepts of biotechnology is need to be further designed.